Genotypic and pheno-metabolomic characterization of a Saccharomyces cerevisiae strain collection - Duarte, Ricardo Franco (2011)
The objective of the present work was to gain a deeper understanding of the phenotypic diversity of natural isolates of Saccharomyces cerevisiae, using high-throughput methods in combination with bioanalytical data. A S. cerevisiae strain collection was constituted comprising 187 strains from different geographical origins and technological uses. Some microsatellite alleles and phenotypes were identified as responsible for the highest strain variability. All strains were used for fermentation with white grapes must, and final fermentation products were analysed using fiber optics spectroscopy and bioanalytical quantification. Inter-strain aromatic profiles (primary fermentation products, higher alcohols, esters, fatty acids) were discriminated by HPLC and GC-MS. Relating the metabolic signature of the strains with phenotypic and genetic data by computational analysis is a pre-requisite to obtain a holistic overview of yeast pheno-metabolomics.